The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1945
DOI: 10.1017/s0022172400013280
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological investigation into the causation of diarrhoea and enteritis in Dublin in 1942—3

Abstract: The Group I paracolon bacilli formed biochemically a stable group. They fermented glucose, maltose, mannite, and dulcite, but not saccharose. Most of them could be distinguished from Salmonella organisms by the late fermentation of lactose or the production of indole. Many resembled the Newcastle bacillus in being late-dulcite fermenters. Serologically 75% of the strains were identical, each containing the A antigen. Some formed a separate group containing the A antigen, andBact. alkalescensantigen and the C a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1948
1948
1954
1954

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Four of them did not produce gas in MacConkey's broth a t 37'. This agrees with the results obtained by Stuart, Griffin & Baker (1938), who st,reaked eosin methyleae blue agar plates with decayed parts of fruits and vegetables, and employed incubation a t room temperature for 48 hr. Twenty-four of their 42 cultures produced gas from lactose at room temperature but not a t 37", 5 produced acid alone a t either temperature and only 13 produced acid and gas a t 37".…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Four of them did not produce gas in MacConkey's broth a t 37'. This agrees with the results obtained by Stuart, Griffin & Baker (1938), who st,reaked eosin methyleae blue agar plates with decayed parts of fruits and vegetables, and employed incubation a t room temperature for 48 hr. Twenty-four of their 42 cultures produced gas from lactose at room temperature but not a t 37", 5 produced acid alone a t either temperature and only 13 produced acid and gas a t 37".…”
Section: Discussionsupporting
confidence: 91%
“…a t 44' in a modified Eijkman medium. Mackenzie & Hilton-Sergeant (1938), Bardsley (1938Bardsley ( , 1948, Clegg & Sherwood (1939, 1947, Clegg (1941), Sherwood & Clegg (1942) and Ferramola (1940) have confirmed that Bact. coli type I almost invariably forms gas from lactose in MacConkey's broth a t 44".…”
Section: S B Thomas G Elis Jones and Patricia M Franklinmentioning
confidence: 91%
See 1 more Smart Citation